Sex ratios concepts and research methods - Hardy, Ian (Cambridge University Press, 2002)
Covering sex allocation, sex determination and operational sex ratios, this multi-author volume provides both a conceptual context and an instruction in methods for many aspects of sex ratio research. Theory, statistical analysis and genetics are each explained and discussed in the first three sections. The remaining chapters each focus on research in one of a wide spectrum of animal, plant and microbial taxa, including sex ratio distorting bacteria in invertebrates, malarial parasites, birds, human and other mammals, giving critical appraisals of such research. Sex Ratios: Concepts and Research Methods is primarily intended for graduate and professional behavioural and evolutionary ecologists in this field, but it will also be useful to biologists building evolutionary models, and researchers analysing data involving proportions or comparisons across phylogenetically related species
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sex ratio